FRI0094 Disability in Early Rheumatoid Arthritis May Persist despite Improvement in Disease Activity: Evidence from Yorkshire Early Arthritis Register. (15th July 2016) - Twigg, S.; Hensor, E.; Emery, P.; Tennant, A.; Morgan, A.W.; ,
Abstract : Background: Disability adversely affects the wellbeing of individuals with rheumatoid arthritis (RA) and contributes to direct and indirect health care costs (1). However, owing to substantial advances in drug treatment for RA, management often focuses on suppression of inflammation. In the United Kingdom, treatment with biological agents is guided by disease activity score from counts of 28 joints (DAS28) (2) and EULAR guidance recommends treatment goals of low disease activity or remission (3). Although these targets are of undoubted importance, the relationship between the treatment target (inflammation or disease activity) and disability is not well described. Objectives: 1. Describe the relationship between disease activity and disability over 2 years in early RA 2. Identify predictors of adverse outcome. Methods: Cases with rheumatologist-confirmed early RA were recruited to Yorkshire Early Arthritis Register (YEAR). Data from 1415 patients were applied to separate latent growth curve models of change in DAS28 and disability index of Health Assessment Questionnaire (HAQ-DI) over 2 years. A parallel process growth curve model described how HAQ-DI varied with DAS28. Dual trajectory analysis (4) was used to describe distinct dual trajectories of change in both variables. Predictors of likely dual trajectory group membership were identified using multinomial logistic regression. Results: Two trajectories of DAS28 (high decreasing DAS28 and low decreasing DAS28) and HAQ-DI (high stable HAQ-DI and low decreasing HAQ-DI) were identified, shown in Figure 1 . Four distinct dual trajectory groups were: group 1, high decreasing DAS28 and high stable HAQ-DI (23% of cohort); group 2, high decreasing DAS28 and low decreasing HAQ-DI (1%); group 3, low decreasing DAS28 and high stable HAQ-DI (26%); group 4, low decreasing DAS28 and low decreasing HAQ-DI (50%). Predictors of group 1 membership (compared to group 4) were similar to known predictors of poor outcome in RA: female gender, social deprivation and greater baseline fatigue. Predictors of group 3 membership were the same as group 1, but also included older age and greater overall contribution of tender joint count and visual analogue score to baseline DAS28. Conclusions: Persistence of disability despite improvement in disease activity was more likely in older patients and those with greater subjective components of baseline DAS28. This suggests that current therapies, which target inflammation, may not be sufficient to reduce disability in early RA. Future work should examine the impact of comorbidity and pain on function in early RA. References: Hallert E, Husberg M, Jonsson D, Skogh T. Rheumatoid arthritis is already expensive during the first year of the disease (the Swedish TIRA project). Rheumatology. 2004;43:1374–82. National Institute for Health and Care Excellence. Rheumatoid arthritis: The management of rheumatoid arthritis in adults. 2009. Smolen JS, Landewe R, Breedveld FC, Buch M, Burmester G, Dougados M, et al. EULAR recommendations for the management of rheumatoid arthritis with synthetic and biological disease-modifying antirheumatic drugs: 2013 update. Ann Rheum Dis. 2014;73:492–509. Nagin DS, Tremblay RE. Analyzing developmental trajectories of distinct but related behaviors: a group-based method. Psychol Methods. 2001;6:18–34. Disclosure of Interest: None declared